1997
DOI: 10.1076/ceyr.16.3.177.15406
|View full text |Cite
|
Sign up to set email alerts
|

Immunolocalization of transforming growth factor-a and its receptor in the normal and hyperoxia-exposed neonatal rat retina

Abstract: Our findings of altered expression of TGF-alpha and EGF-R during retinal development suggests a biological function for this growth factor, possibly promoting retinal cell proliferation, differentiation, and survival. The altered immunolocalization of TGF-alpha and EGF-R in the hyperoxia-exposed retina suggest that TGF-alpha is likely involved in the retinal response to injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

1998
1998
2006
2006

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Since light damage is frequently used as a method to enable efficient culture of M€ uller glia, it is possible that the up-regulation of EGFR, triggered by light damage, contributes to this phenomenon. A study by Powers and Planck (1997) also reported EGFR expression in M€ uller glia in the developing rat retina. However, there was no quantitation in their study, and the localization to Muller glia was not demonstrated with co-labeling for M€ uller glial-specific markers.…”
Section: Discussionmentioning
confidence: 86%
“…Since light damage is frequently used as a method to enable efficient culture of M€ uller glia, it is possible that the up-regulation of EGFR, triggered by light damage, contributes to this phenomenon. A study by Powers and Planck (1997) also reported EGFR expression in M€ uller glia in the developing rat retina. However, there was no quantitation in their study, and the localization to Muller glia was not demonstrated with co-labeling for M€ uller glial-specific markers.…”
Section: Discussionmentioning
confidence: 86%
“…In these studies, EGF was never shown to induce cell degeneration. Although EGF and its receptors are highly expressed in the rat retina during the early postnatal period (Anchan et al, 1991;Powers and Planck, 1997), including in PRs at postnatal day 5 (data not shown), nothing has been reported on EGF effects on postnatal retinal cells in culture. Here, activation of EGFR in PRs was observed clearly by phosphotyrosine immunodetection, providing evidence that EGF promotes postmitotic PR degeneration in vitro.…”
Section: Discussionmentioning
confidence: 96%
“…TGF-a was reportedly found in the normal and affected tissues of the eye, mainly in the retina [10,31,32,35,39]. TGF-a may be involved in the proliferation and differentiation of lens epithelial cells under physiological conditions and after cataract surgery.…”
Section: Discussionmentioning
confidence: 99%